Locusts employ neuronal sensory prioritization to reconcile two conflicting olfactory signals while aggregating - Qiaoqiao Yu; Jing Yang; Jia Yu; Hong Lei; Le Kang; Xiaojiao Guo (Proceedings of the National Academy of Sciences, 2025)
Migratory locusts ( Locusta migratoria ) emit two key odorants during aggregation: 4-vinylanisole (4VA), which serves as an aggregation pheromone attracting conspecifics to form swarms, and phenylacetonitrile (PAN), which acts as an aposematic signal and a precursor of a defense toxin, deterring conspecifics from cannibalism and protecting against predators. However, how locusts reconcile these two conflicting olfactory signals while aggregating is not yet understood. Our study addresses this by examining the release dynamics of the two signals, their behavioral effects, and the neural mechanisms underlying their perception. 4VA is released earlier and at lower locust densities than PAN, with PAN’s release increasing as aggregation progresses. Although PAN’s emission levels eventually exceed those of 4VA, locusts consistently exhibit a preference for the emitted blend, regardless of variations in proportions and concentrations. Notably, increasing amounts of 4VA added to PAN can counteract PAN’s repellent effects, but this is not the case when PAN is added to 4VA. Mechanistically, we found that antennal neurons responsive to 4VA suppress the activity of neurons responsive to PAN. In the antennal lobe, it is the conduction velocities of projection neurons, rather than other neural properties, that are responsible for the observed behavioral pattern, leading to an overall attractive response. Collectively, our findings imply that insects are capable of harmonizing the effects of two distinct pheromones to optimize both social cohesion and chemical defense.